THE PEDAGOGICAL SYSTEM AS A STRUCTURAL COMPONENT OF THE CONTENT OF CHARACTER TRAINING OF SERVICEMEN IN THE MODERN CONTEXT OF THE DEVELOPMENT OF THE ARMED FORCES OF UKRAINE - Ryzhykov, V.; Dobryanskyi, I.; Storubliov, O. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
This scientific article presents different components of the theory of training, particularly: its content, principles, methods and the systematic principles of providing patriotic training to future officers within the system of military education of Ukraine in accordance to modern political realities.The special necessary condition of forming a modern serviceman as an individual are the inter related issues of the aim of training characters and the laws of social development, since the overall development of the personality of the servicemen is the obvious necessity of the Armed Forces taken into account the challenges of the modern world: the scientific-technical progress and the political reality. The material base for the activity of the Armed Forces of Ukraine is to be presented by highly developed, scientifically-technical modern weaponry but in order to organize this type of representation progressive men are needed with a de-blocked technical and innovative potential, that eventually will enable them to manage the modern military equipment.The process of training has been researched as a component of the system of professional training of officers under the modern conditions of the Armed Forces of Ukraine. The theoretic scientific analyses of the content, principles and methods of patriotic education of military personel have been conducted. The meaning of patriotism and its impact on the effective professional activity of the officer of the Armed Forces has been defined.The methodological basis for the process of patriotic education of officers is the scientific theory of experiencing that predetermines the unity of history and logic within the framework of a pedagogical process, the methodological analyses of dedictical definitions, facts, events and methodological content on training of officers, the knowledge of theoretic basics of the normative-educational disciplines, the implementation of the cycle of practical and tactical training.The modern system of education aimed at patriotism among service men is to be governed by the following principles: the civic-oriented nurturing process, a connection between developing a personality and the peculiarities of military service, based on the positive features of an educational process, the humanization of education, the unity of educational influences.The main aim of higher military education is to promote the development of an officer – a true patriot and a profound professional of his cause that is capable to independently point out and solve professional issues in the so called society of risks.
Keywords: the theory on educating officers, patriotism, content and principles of education, the training of service men